Asymmetric Inferior Predilection of Lisch Nodules With Unilateral Ptosis. Issue 1 (March 2020) - Egan, Robert A.
Abstract : Abstract: Lisch nodules are melanocytic hamartomas that have been hypothesized to grow larger in the presence of sunlight. A 17-year-old boy with neurofibromatosis Type 1 and congenital ptosis in one eye presented and was found to have a distinct asymmetry of Lisch nodules between eyes with less under the ptotic lid. This case supports the theory that Lisch nodules form at least partially due to a direct trophic effect of sunlight.